41‐2: Invited Paper: Recent Developments in Inkjet‐printed OLEDs for High Resolution, Large Area Applications. Issue 1 (25th September 2020) - Kang, Jin-goo; Koo, Youngmo; Ha, Jaekook; Lee, Changhee
Abstract : RGB printing method has been widely regarded as a potential tool for manufacturing high resolution, large size OLED applications, with the help of recent progresses of soluble OLED materials and ink‐jet printing equipment. However, there are still technical hurdles which remain in order for inkjet‐printed OLED displays to move from prototype to mass production scale. In this report, recent R&D trends will be reviewed of device performances, ink‐jet printing equipment, as well as inkjet‐printed OLED products recently demonstrated by display panel makers for various applications. Moreover, key technical issues will be discussed to be overcome in order for mass production, such as an ink formulation, a high resolution ink‐jet printing, inter‐mixing between printed layers, thickness uniformity of printed layers, etc. Lastly, our recent progress will be presented, of a power consumption, color gamut, and lifetime of inkjet‐printed panel with pixel resolution over 200ppi.